The Mode of Speech Acts in the Film â€œTanah Surga Katanyaâ€ by Danial Rifki - Hayati, Itsnaini Nur; Rustono, Rustono (Universitas Negeri Semarang, 2021)
This study aims to find the form of the speech mode in the film